Nasopharyngeal bacterial carriage and antimicrobial resistance in underfive children with community acquired pneumonia (Faculty of Medicine Universitas Indonesia, 2002)
Pathogens in nasopharynx is a significant risk factor of pneumonia. According to WHO, isolates to be tested for antimicrobial resistance in the community should be obtained from nasopharyngeal (NP) swabs. The aim of this study is to know the bacterial patterns of the nasopharynx and cotrimoxazole resistance in under five-year old children with community acquired pneumonia. The study was carried out in 4 primary health clinic (Puskesmas) in Majalaya sub-district, Bandung, West Java, Indonesia. All underfive children with cough and/or difficult breathing and classified as having non-severe pneumonia (WHO guidelines) were placed in Amies transport medium and stored in a sterile jar, before taken to the laboratory for further examination, in the same day. During this nine month study, 698 children with clinical signs of non-severe pneumonia were enrolled. About 25.4% (177/698) of the nasopharyngeal specimens yielded bacterial isolates; i.e. 120 (67.8%) were positive for S pneumoniae, 21 for S epidermidis and alpha streptococcus, 6 for Hafnia alvei, 5 for S aureus, 2 for B catarrhalis, and 1(0.6%) for H influenza and Klebsiella, respectively. The antimicrobial resistance test to cotrimoxazole showed that 48.2% of S pneumoniae strain had full resistance and 32.7% showed intermediate resistance to cotrimoxazole. This result is almost similar to the other studies from Asian countries. It seems that H influenza is not a problem in the study area, however, a further study is needed. (Med J Indones 2002; 11: 164-8) Keywords: nasopharyngeal swab, S pneumoniae, cotrimoxazole